Community Based Tourism: Community-Based Ecotourism Governance And Local Wisdom In Musi Rawas District - Mardi Murahman; Muhammad Dimas Rizqi; Nindila Dwi Oriena; Alda Azaahra (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This study examines the governance of community-based ecotourism (Community Based Tourism/CBT) integrated with local wisdom in Pasenan Village, Musi Rawas Regency. Ecotourism is viewed not only as a tourism activity but also as a means of environmental conservation and community welfare improvement. Findings from observations, interviews, and FGDs indicate that the success of tourism management is largely determined by the synergy between natural potential, community participation, and government support. Local wisdom in the form of knowledge, values, and traditions serves as an essential asset in maintaining the balance between economic utilization and environmental preservation. However, challenges such as limited infrastructure, weak management, and unequal distribution of benefits remain significant obstacles. Quantitative analysis using SmartPLS shows that the research instruments meet validity and reliability criteria, with most indicators having loading factors and AVE values above the standard thresholds. This confirms that ecotourism governance and local wisdom significantly influence the strengthening of CBT. Therefore, the development of ecotourism in Pasenan Village requires strategies that integrate sustainability, empowerment, conservation, and local wisdom to enhance community welfare while preserving cultural and environmental sustainability.